Comparison of Larval Therapy and Vacuum-Assisted Closure Therapy after Revascularization in Peripheral Artery Disease Patients with Ischemic Wounds. (29th March 2022) - Cangel, Ugur; Sirekbasan, Serhat; Polat, Erdal
Abstract : Objective . Even for very successful peripheral revascularization therapy, treatment is not complete until the ulcerative, gangrenous, and infected wound is closed. This study was performed and compared the outcomes of vacuum-assisted closure (VAC) and maggot debridement therapy (MDT) following peripheral revascularization to accelerate the wound healing process. Methods . We did a prospective randomized clinical trial between January 1, 2014, and June 21, 2019. This study included 72 patients (63 males and nine females). Balloon angioplasty was performed in 21 patients (29.2%), peripheral bypass in 39 (54.2%), and both balloon angioplasty and revascularization (hybrid) surgery in 12 (16.7%). Thirty-three patients (45.8%) received 15 VAC therapy sessions for a month. Therapy progress was monitored at 48 h intervals, and wound debridement was performed. Thirty-nine patients (54.2%) received an average of six larval therapy sessions for a month. Groups were compared with the X 2 test, and a statistically significant difference was found (P < 0.001 ). Results . In the VAC therapy group ( n = 33), 14 patients (42.4%) had their feet amputated, 5 (15.1%) had a toe amputated, and 4 (12.1%) had all of their toes amputated. A skin graft was performed on four patients (12.1%) who developed granulation tissue. The wounds of six patients (18.2%) undergoing VAC therapy healed. In the larval therapy group ( n = 39), the wounds healed in 36 patients (92.3%), and 3 (7.7%) had a toe amputated. Conclusion . Larval therapy was shown to be more effective than VAC therapy for the treatment of postrevascularization ischemic wounds. Thus, larval therapy can be used as an effective biological treatment method when major amputation is not required.